Unilateral Abducens Nerve Palsy with Ipsilateral Horner’s Syndrome as an Initial Manifestation of Recurrent Nasopharyngeal Carcinoma - Top Karti, Dilek (Neuroophthalmology, 2019)
A 62-year-old man was admitted to our clinic with a two-week history of double vision. Neuro-ophthalmological examination showed a left abducens nerve palsy with an ipsilateral Horner’s syndrome. Neuro-imaging identified recurrent nasopharyngeal carcinoma explaining the clinical findings. Co-existence of unilateral abducens nerve palsy and ipsilateral Horner’s syndrome is very rare and localises to the posterior cavernous sinus. Therefore, clinicians should be aware of this rare co-existence and perform appropriate neuro-imaging to clarify the underlying aetiology.